2013
DOI: 10.1039/c3dt32988g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free dehydrogenation of amine–boranes by an N-heterocyclic carbene

Abstract: The dehydrogenation of primary and secondary amine-boranes (RNH(2)·BH(3) and R(2)NH·BH(3); R = alkyl groups) was studied using the bulky N-heterocyclic carbene IPr (IPr = [(HCNDipp)C:]; Dipp = 2,6-(i)Pr(2)C(6)H(3)) as a stoichiometric dehydrogenation agent. In the case of primary amine-boranes, carbene-bound adducts IPr·BH(2)-NH(R)-BH(3) were obtained in place of the desired polymers [RNH-BH(2)](n). The secondary amine-borane (i)Pr(2)NH·BH(3) participated in dehydrogenation chemistry with IPr to afford the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 69 publications
9
33
0
Order By: Relevance
“…The group of Rivard extended the scope of this NHC chemistry and found that N‐heterocyclic carbene 27 (Scheme ) can dehydrogenate MeNH 2 ⋅BH 3 and i PrNH 2 ⋅BH 3 forming the expected NHC–H 2 adduct 28 together with the carbene‐bound B–N–B adduct NHC⋅BH 2 NH(R)−BH 3 ( 29 ) in a 1:1 ratio . The formation of 29 was proposed to proceed through a sequence of events.…”
Section: Stoichiometric Dehydrogenationsupporting
confidence: 87%
“…The group of Rivard extended the scope of this NHC chemistry and found that N‐heterocyclic carbene 27 (Scheme ) can dehydrogenate MeNH 2 ⋅BH 3 and i PrNH 2 ⋅BH 3 forming the expected NHC–H 2 adduct 28 together with the carbene‐bound B–N–B adduct NHC⋅BH 2 NH(R)−BH 3 ( 29 ) in a 1:1 ratio . The formation of 29 was proposed to proceed through a sequence of events.…”
Section: Stoichiometric Dehydrogenationsupporting
confidence: 87%
“…Poly( N ‐methylaminoborane) [MeNH‐BH 2 ] n has been reported to give a broad 11 B NMR resonance at δ =−6.5 ppm in CDCl 3 with no discernable B,H coupling in the proton‐coupled 11 B{ 1 H} NMR spectrum . This chemical shift is similar to that of the six‐membered [MeNH‐BH 2 ] 3 ring (triplet at δ =−5.4 ppm in [D 6 ]acetone, 1 J (B,H)=107 Hz; δ =−5.9 ppm in [D 8 ]THF) . As a broad triplet resonance was located at δ =−4.7 ppm that featured a spectral tail that extends upfield to approximately δ =−6.2 ppm, we decided to investigate the possible formation of [MeNH‐BH 2 ] x oligomers.…”
Section: Resultsmentioning
confidence: 97%
“…The metal‐free dehydrogenation of amine‐boranes has also been reported by Manners and coworkers, where they observed that the monomeric aminoborane i Pr 2 N=BH 2 can behave as a hydrogen acceptor; thus, allowing stoichiometric hydrogen transfer to occur from amine‐borane adducts under ambient conditions . Moreover, our group has shown that N‐heterocyclic carbenes (NHCs) are able to effectively remove H + /H − equivalents from amine‐boranes . In addition, very promising examples of both Lewis acid (B(C 6 F 5 ) 3 ) and Lewis base (proton sponge; 1,8‐(Me 2 N) 2 C 10 H 6 ) promoted dehydrocoupling of amine‐boranes have been developed by the groups of Baker and Sneddon, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reacting the less bulky L Mes (NH)BH 3 (1 A) with the sterically unhindered L Me4 , a triplet in the 11 B NMR spectrum (d = À19.7 ppm, J = 89 Hz) indicates BDF and in the 1 H NMR spectrum L Me4 (H 2 ) is clearly identified. [12] As already demonstrated by the successful isolation of 2 Ab as well as of 2 Ba, the boost of steric hindrance for either ligand (the imino group or the NHC) results in clean BDF (entries Ab and Ba). Apparently, a certain degree of steric congestion at the boron center is required for the BDF to proceed in a controlled manner.…”
mentioning
confidence: 81%
“…Inspired by related reports of Rivard, [4,12] Manners, [13] and Harder, [14] we targeted the synthesis of electron-donating imino ligand-stabilized borane dihydrides of type IV (Scheme 1) as a precursor for the RER through a dehydro-genative route. We introduced the imidazolin-2-imino group {L R1 (N), with L R1 = 1,3-R 1 2 -imidazolin-2-ylidene, R 1 = 2,6-diisopropylphenyl (Dipp) or 2,4,6-trimethylphenyl (Mes)} to borohydride by conversion of L R1 (NH) with borane dimethylsulfide adduct (see the Supporting Information for full experimental details).…”
mentioning
confidence: 99%